Co-regulatory roles of decaying logs and gap positions in modulating soil enzyme activities in forests ecosystems - Qin Wang; Josep Peñuelas; Zhuang Wang; Rui Cao; Lifeng Wang; Wanqin Yang (Plant and Soil, 2026)

Log decomposition and forest gaps synergistically shape the structure and function of wood-inhabiting microbial communities in forest ecosystems - Qin Wang; Zhuang Wang; Josep Peñuelas; Rui Cao; Lifeng Wang; Wanqin Yang (Applied Soil Ecology, 2025)

A systematic review of drying in aquatic products - Junpeng Zeng; Yu Song; Peixu Cong; Yunrui Cao; Jie Xu; Changhu Xue (Reviews in Aquaculture, 2024)
Drying is an essential method for the process and storage of aquatic products. With the removal of water, the occurrence of oxidation, hydrolysis and browning reaction also accompanies it. This article reviews the applications of emerging drying methods in aquatic products, emphasising high‐quality drying. In addition, it summarises the effects of the drying process on the quality of aquatic products, including appearance, nutritional components, flavour and microorganisms. Especially, non‐destructively monitoring technologies are introduced and discussed, including near‐infrared spectroscopy, Raman spectroscopy, hyperspectral imaging, low‐field nuclear magnetic resonance and computer vision system, which are applied to detect and predict the quality of aquatic products. A comprehensive review of recent advances in the research of the drying process of aquatic products is presented, and some perspectives are made for future research.

A comprehensive review of oyster peptides: Preparation, characterisation and bioactivities - Lili Hao; Xincen Wang; Yunrui Cao; Jie Xu; Changhu Xue (Reviews in Aquaculture, 2022)
Oysters are a healthy and excellent source of lean protein (content up to 45%–57%). In addition, polypeptides extracted from hydrolysis of oyster protein by enzymatic hydrolysis or fermentation have diverse bioactivities, such as antioxidant, antimicrobial, antihypertensive, promoting sexual reproduction, anti‐inflammatory and anticancer. However, there are still great challenges in the preparation and characterisation of oyster polypeptides. Besides, the bioactivities and the corresponding underlying mechanisms of oyster peptides (OPs) have not yet been fully described. In order to obtain more specific peptides with potential bioactivities, optimisation of conditions employed during hydrolysis of oyster protein is therefore necessary, as well as the identification of the amino acid sequence and secondary structure of OPs. This review discusses latest research progress in preparation (including production, isolation and purification) and characterisation of OPs, with emphasis on their multiple bioactivities. Mechanisms underlying such bioactivities have also been presented. Comprehensive information about OPs could pave the way towards a functional development and more efficient utilisation of oysters. Collectively, there is growing evidence that OPs have potential health benefits. More research efforts are needed to determine their potential use in many contexts and ultimately develop more efficient and safer OP‐based products.